2023
DOI: 10.1038/s41541-023-00675-1
|View full text |Cite
|
Sign up to set email alerts
|

A candidate subunit vaccine induces protective immunity against Mycobacterium avium subspecies paratuberculosis in mice

Abstract: Mycobacterium avium subspecies paratuberculosis (MAP) causes paratuberculosis (PTB), which is a granulomatous enteritis in ruminants that threatens the dairy industry’s healthy development and public health safety worldwide. Because the commercial inactivated vaccines are not completely protective and interfere with bovine tuberculosis diagnostics, we tested four fusion proteins, namely 66NC, 66CN, 90NC, and 90CN, which were constructed with MAP3527, Ag85B, and Hsp70 of MAP in different tandem combinations. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The immune protection against R. equi infection does not rely exclusively on the CD4 + Th1 lymphocyte response [ 46 ]. As with M. tb , IFN-γ-positive CD8 + T lymphocytes also contribute to immune clearance during pulmonary challenge by virulent R. equi [ 47 , 48 ]. In this study, FCM was used to detect antigen-specific IFN-γ and TNF-α in splenic T lymphocytes, and the proportions of IFN-γ- and TNF-α-positive CD4 + and CD8 + T lymphocytes were significantly increased after immunization.…”
Section: Discussionmentioning
confidence: 99%
“…The immune protection against R. equi infection does not rely exclusively on the CD4 + Th1 lymphocyte response [ 46 ]. As with M. tb , IFN-γ-positive CD8 + T lymphocytes also contribute to immune clearance during pulmonary challenge by virulent R. equi [ 47 , 48 ]. In this study, FCM was used to detect antigen-specific IFN-γ and TNF-α in splenic T lymphocytes, and the proportions of IFN-γ- and TNF-α-positive CD4 + and CD8 + T lymphocytes were significantly increased after immunization.…”
Section: Discussionmentioning
confidence: 99%
“…The development of recombinant subunit vaccines, comprising highly effective antigen compositions generated through diverse expression systems, has garnered increasing attention in recent years [ 24 , 25 ]. Subunit vaccines are considered safer as they do not contain live pathogens and lack the ability to replicate in the organism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6]. Shao et al [7] reported differences in the CFU load in the liver from 2 to 8 w.p.i with the intraperitoneal route, with no bacterial recovery after that. They also detected differences in weight gain among the groups from 2 to 12 w.p.i.…”
Section: Mouse Modelmentioning
confidence: 99%